Synthesizing Tradition and Technology in Pesantren Curriculum: A Case Study at Pesantren Al-Falah Situbondo - Musaddad, Ahmad (Institut Darul Falah Bandung Barat, 2025)
Pesantren face increasing demands to preserve Islamic traditions while equipping santri with digital literacy and global competencies. This study examines how Pesantren Al-Falah Situbondo adapts its curriculum by integrating classical learning with technological and entrepreneurial innovation. Using a qualitative case study supported by descriptive survey data, the research identifies three dynamics: the persistence of memorization-based pedagogy, fragmented adoption of digital tools, and sporadic entrepreneurship initiatives. These findings reveal that curriculum reform in pesantren is not a replacement of tradition but a negotiated synthesis that connects heritage with contemporary skills. Theoretically, the study offers a framework for integrating Islamic values with global competency models, thereby bridging domains that are often treated as separate. Practically, it provides pesantren leaders and policymakers a blueprint for embedding digital literacy and entrepreneurship into lesson plans without undermining religious identity. This model can guide other pesantren in designing adaptive curricula and inform Islamic education policy aimed at preparing graduates who are both rooted in tradition and ready for global engagement.